Reintroducing rewilding to restoration – Rejecting the search for novelty. (May 2019) - Hayward, Matt W.; Scanlon, Robert J.; Callen, Alexandra; Howell, Lachlan G.; Klop-Toker, Kaya L.; Di Blanco, Yamil; Balkenhol, Niko; Bugir, Cassandra K.; Campbell, Lachlan; Caravaggi, Anthony; Chalmers, Anita C.; Clulow, John; et al.
Abstract: Rewilding is emerging as a major issue in conservation. However, there are currently a dozen definitions of rewilding that include Pleistocene rewilding, island rewilding, trophic rewilding, functional rewilding and passive rewilding, and these remain fuzzy, lack clarity and, hence, hinder scientific discourse. Based on current definitions, it is unclear how the interventions described under the rewilding umbrella differ from those framed within the long-standing term 'restoration'. Even projects held up as iconic rewilding endeavours invariably began as restoration projects (e.g., Oostvaaderplassen; Pleistocene Park; the return of wolves to Yellowstone, etc.). Similarly, rewilding organisations (e.g., Rewilding Europe) typically began with a restoration focus. Scientific discourse requires precise language. The fuzziness of existing definitions of rewilding and lack of distinction from restoration practices means that scientific messages cannot be transferred accurately to a policy or practice framework. We suggest that the utility of 'rewilding' as a term is obsolete, and hence recommend scientists and practitioners use 'restoration' instead. Highlights: The term 'rewilding' has over a dozen definitions and existing 'rewilding' projects invariably began as restoration projects. All existing 'rewilding' definitions fit within existing definitions of the long-established field of restoration. Fuzzy and vague definitions impinge upon scientific progress. We recommend using the clearly defined term restoration instead of rewilding.